The identity of Rana lutea Molina, 1782 (Amphibia, Anura) - Ferraro, Daiana P.; Lavilla, Esteban O. (Zootaxa, 2013)
Rana lutea is one of the two anuran species described in 1782 by the Chilean born priest and naturalist Juan Ignacio Molina, and its nomenclatural history is confusing. After a detailed revision of the pertinent literature, we demonstrate that Bufo thaul Schneider, 1799, is a junior objective synonym of Rana lutea Molina, 1782, but based on the usage of both nomina, we revert the precedence and consider Rana lutea Molina, 1782 as a nomen oblitum whereas Bufo thaul Schneider, 1799 is a nomen protectum. Thus, the authorship of the species currently known as Pleurodema thaul (Lesson, 1826) changes to Pleurodema thaul (Schneider, 1799).